Act your age: reading and performing Shakespeare's ageing women - Waters, C (2013)
This thesis provides the first study of the representation, performance, and reception of Shakespeare’s ageing women in early modern and present-day England. It contributes an exposition of the physiology and theory of early modern ageing, drawing on this original material to make an argument for the ageing woman as a source of anxiety within the plays as they were originally staged, and as they are performed and received today. It finds the old and ageing woman in Shakespeare’s drama to be represented as physically and verbally excessive; the thesis also identifies a corresponding urge in the plays and in their reception towards the ageing woman’s containment and control. This containment is exercised in the text, the rehearsal room, the theatre, and the public space of performance reviews. My introduction determines my methodology and establishes the terms of reference for the project. The first chapter defines early modern old age and delivers a study of the early modern literature and theory of the ageing body. Each of the four subsequent chapters explores an ageing female character or characters through the lens of a theme: magic, motherhood, sexuality, and memory. The characters studied are drawn from The Merry Wives of Windsor, Macbeth, The Winter’s Tale, Coriolanus, King John, All’s Well That Ends Well, Antony and Cleopatra, Hamlet, and Richard III. Some brief concluding remarks complete the thesis. The larger project of the thesis is a cultural study. Throughout, I am keen to learn how characters are talked about as well as written and performed. My effort to understand the work which Shakespeare’s older women are asked to carry out in the present day defines my methodology: I draw on prompt books, production recordings, reviews, costume, photographs, programmes, and interviews with actors and directors to aid my investigation, juxtaposing these with close study of the written plays and the early modern culture and knowledge which underpins them. The word count, exclusive of bibliography but inclusive of all footnotes and an appendix, is approximately 92,000.